Combining Drought Survival via Summer Dormancy and Annual Biomass Productivity in Dactylis glomerata L. - Kallida, Rajae; Zhouri, Latifa; Volaire, Florence; Guerin, Adrien; Julier, Bernadette; Shaimi, Naima; Fakiri, Malika; Barre, Philippe (Frontiers in Plant Science, 2016)
Under Mediterranean climates, the best strategy to produce rain-fed fodder crops is to develop perennial drought resistant varieties. Summer dormancy present in native germplasm has been shown to confer a high level of survival under severe drought. Nevertheless it has also been shown to be negatively correlated with annual biomass productivity. The aim of this study was to analyse the correlations between summer dormancy and annual biomass productivity related traits and to identify quantitative trait loci (QTL) for these traits in a progeny of a summer dormant cocksfoot parent (Kasbah) and a summer active parent (Medly). A total of 283 offspring and the parents were phenotyped for summer dormancy, plant growth rate and heading date in Morocco and for maximum leaf elongation rate (LERm) in France. The individuals were genotyped with a total of 325 markers including 59 AFLP, 64 SSR and 202 DArT markers. The offspring exhibited a large quantitative variation for all measured traits. Summer dormancy showed a negative correlation with both plant growth rate (-0.34 p<0.005) and LERm (-0.27 p<0.005). However, genotypes with both a high level of summer dormancy and a high level of plant growth rate were detected in the progeny. One genetic map per parent was built with a total length of 377 and 423 cM for Kasbah and Medly, respectively. Both different and co-localised QTL for summer dormancy and plant growth rate were identified. These results demonstrate that it should be possible to create summer dormant cocksfoot varieties with a high annual biomass productivity.